2019
DOI: 10.58997/smc.v28i1.50
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Influences on Student Newspapers: A Survey of Newspapers of ACEJMC Programs

Abstract: Surveys of student editors, faculty advisers and academic affairs administrators of journalism and mass communication programs accredited by the Accrediting Council on Education in Journalism in Mass Communication suggest that influences at the organizational level do have an impact on the content of student newspapers. The findings show that student editors were more likely to self-censor content when they did not have primary control of the newspapers. Significant differences were found to exist between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Despite the continual rejection of such practices in the courts, university administrators still attempt to control student press messages by cutting funding to news outlets, hiring advisors who are motivated to align with administrative perspectives, and leveraging advisory committees for heavy-handed organizational oversight (Kasior & Darrah, 1996). Administrative hostility promotes self-censorship (Bickham & Shin, 2013). Student newsroom leaders sometimes make editorial decisions based on fear of adverse action (Farquhar & Carey, 2019) or the discomfort of faculty advisers (Filak, 2012).…”
Section: Threats To Campus News Independencementioning
confidence: 99%
“…Despite the continual rejection of such practices in the courts, university administrators still attempt to control student press messages by cutting funding to news outlets, hiring advisors who are motivated to align with administrative perspectives, and leveraging advisory committees for heavy-handed organizational oversight (Kasior & Darrah, 1996). Administrative hostility promotes self-censorship (Bickham & Shin, 2013). Student newsroom leaders sometimes make editorial decisions based on fear of adverse action (Farquhar & Carey, 2019) or the discomfort of faculty advisers (Filak, 2012).…”
Section: Threats To Campus News Independencementioning
confidence: 99%
“…It does not delve into questions of censoring practices or lived experiences. Overall, college newspaper editors perceive themselves as having more control over the content of their newspapers than institutional faculty or administration, and faculty advisers and administrators agree that control is generally in students' hands (Bickham & Shin, 2013;Enloe, 2011;Bodle, 1997). For example, in a survey of daily student newspaper advisers and business managers, 81.4% reported that their institutions did not have influence over the newspaper's content (Bodle, 1997).…”
Section: College Student Perceptionsmentioning
confidence: 99%
“…These studies suggest that involved actorsincluding editors, advisers, and administratorsperceive student editors to have the main thrust of editorial control over campus newspapers. However, one study that asked participants whether they view censorship as a problem at their newspapers found that editors tend to agree that censorship is a problem for their publications, but advisers (61%) and administrators (81%) overwhelmingly do not report that censorship is a problem at their institutions' student newspapers (Bickham & Shin, 2013). This indicates that there is dissonance between whom editors perceive to have control over student publications and whether they perceive censorship to be a problem at their publications.…”
Section: College Student Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations